2003
DOI: 10.1103/physrevb.68.014425
|View full text |Cite
|
Sign up to set email alerts
|

Ion pairs and spontaneous break of symmetry in the valence-fluctuating compoundYbB12

Abstract: Electron spin resonance ͑ESR͒ from Yb 3ϩ ions in a single crystal of fluctuating valence compound YbB 12 was studied. We have observed two main lines symmetrically displaced from a g value of 2.55 and exhibiting modulation with 5% anisotropy, when the magnetic field was rotated in the ͑110͒ plane from the cubic axis to the ͓110͔ direction. Experimental results are explained by an existence of Yb-Yb pairs which are coupled by isotropic exchange but interact also with the other pairs by dipole and exchange coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…For instance, noticeable anisotropy of magnetoresistance has been revealed in LuB 12 [13]. As reported in [14], where the narrow-gap semiconductor YbB 12 was studied by the technique of electron paramagnetic resonance, the Yb 3+ -Yb 3+ pairs appeared at low temperatures along certain directions being accompanied by shifts of the cations from the inversion centers.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For instance, noticeable anisotropy of magnetoresistance has been revealed in LuB 12 [13]. As reported in [14], where the narrow-gap semiconductor YbB 12 was studied by the technique of electron paramagnetic resonance, the Yb 3+ -Yb 3+ pairs appeared at low temperatures along certain directions being accompanied by shifts of the cations from the inversion centers.…”
Section: Introductionmentioning
confidence: 79%
“…[101] direction that allows to make a reference to the Yb 3+ -Yb 3+ pairs bounded in a certain direction in the crystal of YbB 12 [14].…”
Section: Mem Resultsmentioning
confidence: 99%
“…A noticeable change in both the ADPs of boron atoms and in the sizes of B 12 clusters and the distances between them at T c ' 140 K confirms earlier conclusions made by Kalvius et al (2002Kalvius et al ( , 2003 and Sluchanko et al (2011) on the development of lattice instability in YbB 12 in the vicinity of T c . It should be added that the electron spin resonance (EPR) spectra of YbB 12 were studied by Altshuler et al (2003). The ground state of the Yb 3+ ion was identified as the G 6 state, which should be isotropic in a cubic crystal but was actually modulated and split by a slight anisotropic correction.…”
Section: Structure-properties Relationshipmentioning
confidence: 99%
“…The ground state of the Yb 3+ ion was identified as the G 6 state, which should be isotropic in a cubic crystal but was actually modulated and split by a slight anisotropic correction. The experimental results were explained by Altshuler et al (2003) as the existence of Yb-Yb pairs connected by isotropic exchange and interacting with other Yb-Yb pairs through dipole and exchange interactions. The concentration of Yb 3+ ions in these pairs was estimated to be 0.2-0.5% and the origin the EPR signal has been attributed to the effect of defects and/or vacancies stabilizing the 3+ valence of Yb ions instead of the intermediate 2.92-2.95 valence.…”
Section: Structure-properties Relationshipmentioning
confidence: 99%
“…[31] The INS results confirm the low-dimensional anisotropy in this SCES with fcc crystal structure, and the value 𝜉 || ∼ 5.4 Å correlates very well with the shortest Yb-Yb distance in the fcc lattice. It is also worth noting that a strong increase of the signal of electron spin resonance (ESR) was observed previously in YbB12, [32] and the temperature dependence of the ESR amplitude was found to be close to exponential increase with a characteristic temperature of ∼ 18 K, which is close to 𝑇s ∼ 15 K. The authors [32] concluded that the ESR results can be understood assuming the existence of Yb 3+ ion pairs coupled by isotropic exchange interaction, which also interact with neighboring Yb pairs connecting these dimers in the nanoscale channels. Thus, the chains of Yb pairs in the metallic channels were predicted previously in various independent experiments.…”
Section: -3mentioning
confidence: 56%